Pengembangan Lembar Kerja Peserta Didik Berbasis Discovery Learning dalam Pembelajaran IPA untuk Meningkatkan Hasil Belajar Kognitif dan Keterampilan Proses SAINS Siswa Kelas V - Eka Susanti; Irwan Koto; Agus Susanta (UNIB Press, 2023)
The purpose of the study was to describe the feasibility of discovery learning based student worksheets in science learning for fifth grade students, to find out student responses to discovery learning based student worksheets in science learning to improve cognitive learning outcomes and science process skills of fifth grade students, to determine the effectiveness of using sheets the work of students based on discovery learning in science learning to improve cognitive learning outcomes and science process skills of class V students. This type of research uses Research and Development (R&D) a process to develop new products or improve existing products so that they can be accounted for. the application of an R & D approach with the method ADDIE. The integration of the discovery learning model in the worksheet elements of students has paid attention to the limitations of students' rational thinking abilities, especially elementary school age students. to help improve cognitive learning outcomes and science process skills using discovery learning models. The questions used were cognitive questions and science process skills questions used for assessment. The difficulty of developing student worksheets based on discovery learning in science learning is at the design stage, especially choosing striking colors on the background and choosing good pictures. With further research, it is necessary to prepare pictures that will be used to support student worksheets.